Removal Of Oxytetracycline From Water Using Ozonation Alone And Combination Of Catalytic Ozonation With Zinc Oxide Nanoparticles - Nadesan, Suvithra (Universiti Sains Malaysia, 2022)
Oxytetracycline (OTCs) antibiotic pollution is a growing global threat to aquatic and terrestrial biodiversity due to its unprecedented use in aquaculture, livestock, and human disease preventation. Antibiotics like OTCs are becoming a serious threat to the environment due to their unaccounted use in sub therapeutic animal growth promotion and human treatment. Tetracyclines (TCs) are class of diverse antibiotics that have a wide range of applications in human, veterinary and aquaculture treatment. The purpose of this study was to compare the efficiency of sole ozonation and catalytic ozonation in the degradation of OTC as an environmental hazards contaminant in an aqueous solution. Zinc oxide (ZnO) nanoparticles were used as a catalytic agent with ozone (ZnO/O3). The influence of operational parameters such as initial antibiotic concentration (10,35,50) mg/l, temperature (15,25,35) °C, pH (3,7,11) and catalyst dosage (25,50,100) mg were investigated in this ozonation process. The ozone supply was constant throughout the experiment which is 600 mg/h. For an initial concentration of antibiotic, the results obtained showed that ozone can degrade OTC antibiotic faster at very low concentration. This is because at higher concentration of antibiotics, there are more formation of intermediates that led to higher consumption of ozone and reaction time. At concentration of 10 mg/l, the degradation efficiency reached almost 75.2% at first 20 minutes of the reaction. At an initial pH of 11, the results showed a gradual increase of percentage on the removal rate of OTC. Almost more than 68. 1 % of antibiotic degraded after 20 minutes of reaction time. For the catalyst weight, higher amount showed the highest degradation efficiency. 100mg of ZnO nanoparticles degraded almost 98.37% of antibiotic within the first 20 minutes. The highest removal rate was observed at temperature of 25°C with degradation efficiency of 54.9 % at the first 20 minutes. The optimum condition for sole condition was 10 mg/l at pH=11 with temperature of 25°C, after 120 min, a 95.8 % of OTC removal was achieved. Concentration of 50 mg/L was used for other parameters to clearly observe the effect on the degradation of antibiotic. Kinetic analysis showed that the ozonation of OTC is identified as the pseudo first order reaction with linear relationship between OTC antibiotic and ozone. It is showed that antibiotic concentration of 50 mg/l with catalytic ozonation reached about 99.5% while for 96.3% of removal rate for sole ozonation at condition at pH=11, temperature of 25°C at 120 minutes reaction. The results demonstrated that catalytic ozonation with zinc oxide nanoparticles was a very effective method for OTC degradation.